2015
DOI: 10.7554/elife.10140
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between kinesin-1 and cortical dynein during axonal outgrowth and microtubule organization in Drosophila neurons

Abstract: In this study, we investigated how microtubule motors organize microtubules in Drosophila neurons. We showed that, during the initial stages of axon outgrowth, microtubules display mixed polarity and minus-end-out microtubules push the tip of the axon, consistent with kinesin-1 driving outgrowth by sliding antiparallel microtubules. At later stages, the microtubule orientation in the axon switches from mixed to uniform polarity with plus-end-out. Dynein knockdown prevents this rearrangement and results in micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
132
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(144 citation statements)
references
References 52 publications
(80 reference statements)
10
132
1
Order By: Relevance
“…In contrast to kinesin-1's function in streaming, dynein is not required for fast streaming; instead, it inhibits the shift from slow streaming to fast streaming (8,9). This KHC-dependent and KLC/dynein-independent streaming mechanism highly resembles another important function of KHC, called microtubule-microtubule sliding, studied by our group (10)(11)(12)(13)(14)(15). In this process, KHC binds one microtubule through its ATPindependent C-terminal-binding site while walking on another microtubule using its ATP-dependent motor domain, as reported by Winding et al (17).…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…In contrast to kinesin-1's function in streaming, dynein is not required for fast streaming; instead, it inhibits the shift from slow streaming to fast streaming (8,9). This KHC-dependent and KLC/dynein-independent streaming mechanism highly resembles another important function of KHC, called microtubule-microtubule sliding, studied by our group (10)(11)(12)(13)(14)(15). In this process, KHC binds one microtubule through its ATPindependent C-terminal-binding site while walking on another microtubule using its ATP-dependent motor domain, as reported by Winding et al (17).…”
mentioning
confidence: 60%
“…1A) and binds to the acidic E-hook of tubulin through an electrostatic interaction (18,19). Furthermore, we have shown that KHC-driven microtubule sliding is independent of KLC and cannot be inhibited by dynein knockdown or dynein inhibition (10,12,14,15).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Live imaging in Drosophila neurons showed that MTs display mixed polarity at the initial stage of axon formation from the cell body, but then reorganize to become predominantly plus-end-distal as axons extend (del Castillo et al, 2015). Similarly, in cultured rat hippocampal neurons, immature neurites have mixed MT polarity and plus-end-distal polarity is established once the axon is specified (Kollins et al, 2009; Yau et al, 2016).…”
Section: Introductionmentioning
confidence: 99%